Editorial - Meyza, Henryk (Études et Travaux, 2021)
The Institute of Mediterranean and Oriental Cultures, Polish Academy of Sciences, represented by one of its legal predecessors, the Research Centre for Mediterranean Archaeology of the Academy, was from the beginning of Polish excavations in Cyprus in 1965 involved in study, publication of finds and storage as well as processing of documentation of Polish research in Cyprus until 2019. The excavations were initiated by the first Director of the Research Centre at the Academy and the Polish Centre of Mediterranean Archaeology of the University of Warsaw in Cairo (a foreign unit of the University), professor Kazimierz Michałowski.